Формированиe международно-правовой основы Палестинского государства в начале 1990-х гг. (Zaporizhzhia Historical Review, 2021)
In the article the author describes reasons and maintenance of Arabic- Israeli conflict, reflects the stages of negotiation process as to its settlement and analyses the role of international and peacemaking organizations in this process.